Mobile Phone Use at School as an Element of Hidden Curriculum: M-Hidden Curriculum - Akpinar, Burhan; Batdi, Veli; Yıldırım, Bilal; Kuloglu, Aysenur; Özeren, Ender (Common Ground Research Networks, 2016)
Mobile phone is a new educational phenomenon that can be related with students' health, academic and social development. There a number of studies in literature on this subject. However, there aren't any studies on the relation of mobile phone with informal processes at school. Mobile phone is a new phenomenon which builds school culture with informal ways or reproduces the existing culture. The relation of this element with the hidden curriculum at school is disputable. The aim of this study is to determine the views of high school students in Turkey on the reasons of their mobile phone use in the context of hidden curriculum and evaluate those views in terms of different variables. The study was carried out on 289 students enrolled at state schools in the cities of Elazig and Malatya in 2013-2014 educational year. The data obtained via a questionnaire form were analyzed using SPSS package program. As a result of the analysis, it was determined that most of the high school students in Turkey have mobile phones and they bring them into classes although it is banned by the regulations. Students prefer to use mobile phones to communicate, listen to music, share announcements, send text messages, take photos, connect to social networks and for educational purposes. These preferences are, in a sense, means of building a school culture or reproducing it, which is described as hidden curriculum. This case can be considered as the sign of a new hidden curriculum, being built by mobile phones informally. This curriculum can be named as m-hidden curriculum or e-hidden curriculum. © 2016 International Journal of Learning and Teaching. All Rights Reserved.
Keywords: ehidden curriculum; hidden curriculum; m-hidden curriculum; mobile learning; mobile phone; mobile school culture